Fish adjust aggressive behavior to audience size with limited information on bystanders’ fighting ability - Falsarella, Ludmilla do Nascimento [UNESP]; Brandão, Manuela Lombardi [UNESP]; Gonçalves-de-Freitas, Eliane [UNESP] (Elsevier, 2017)
In a social environment, individual behavior is modulated by surrounding observers (a phenomenon known as the audience effect). Here, we used mirrors to test the effect of two audience sizes (one virtual bystander vs. three virtual bystanders) on the aggressive behavior of a focal fish when bystander's fighting ability was not clear (i.e., information about the ability of virtual conspecifics limited by their mirror images). We found that the Nile tilapia, a cichlid fish, responds to its image as an audience by reducing overt aggression in the presence of larger audience.
Keywords: Bystander; Mirror-elicited image; Social network